Averaging of the Neumann problems for nonlinear elliptic equations in domains with accumulators - Kovalevskii, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the asymptotic behavior of solutions of the Neumann problems for nonlinear elliptic equations in domains with accumulators, which simulate porous media. An effective description is given for an averaged problem, which, in the case of simple accumulators, is a problem for the system of a functional equation and a differential equation; in the case of double accumulators, it is a problem for the system of two functional equations and a differential equation.